2021
DOI: 10.17221/44/2020-pps
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria leaf spot of broccoli caused by Alternaria alternata in Bangladesh

Abstract: This study aimed to isolate and characterise the pathogen associated with Alternaria leaf spot on broccoli and to evaluate the inhibitory effects of fungicides against it. We isolated and identified the fungal pathogen as Alternaria sp. using morphological and cultural methods. Based on the aligned sequences of the internal transcribed spacer (ITS) and molecular phylogenetic analysis by the neighbour-joining method, the isolates (Ab1 and Ab2) were confirmed as Alternaria alternata. The conidia of the isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Specifically, endophytes capable of producing auxin exhibit a red/pink color change upon addition of Salkowski’s reagent, attributed to the interaction between auxin and iron resulting in complex compound formation. Previous studies have documented the auxin-producing abilities of Aspergillus 26 , Talaromyces 27 , Fusarium 28 , and Alternaria 29 species. This study represents the first documentation of A. bicephalus’s capacity to produce auxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, endophytes capable of producing auxin exhibit a red/pink color change upon addition of Salkowski’s reagent, attributed to the interaction between auxin and iron resulting in complex compound formation. Previous studies have documented the auxin-producing abilities of Aspergillus 26 , Talaromyces 27 , Fusarium 28 , and Alternaria 29 species. This study represents the first documentation of A. bicephalus’s capacity to produce auxin.…”
Section: Discussionmentioning
confidence: 99%
“…27 , Fusarium 28 , and Alternaria29 species. This study represents the rst documentation of A. bicephalus's capacity to produce auxin.…”
mentioning
confidence: 99%
“…This method shows the effect of the solubility of the compounds in a PDA medium. The diameter of fungus growth on PDA (in mm) with and without the compounds (control) was measured as described by (Nira et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Wijayawardene et al [ 14 ] reported that Alternaria contains 366 accepted and recognizable species. Alternaria black spot, blight disease, and seed-borne pathogens are major pathogens distributed worldwide on cruciferous crops and other economically relevant plants that cause considerable yield losses [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%